Pengaruh Interaksi Sosial Teman Sebaya Terhadap Tingkah Laku Salah Suai Peserta Didik di Kelas XI IPS SMAN 2 Tebo - Afifah, Afifah (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study is to know the students' learning difficulties by grade VI students. The research approach used is qualitative approach. The subject of this research is the students of grade VI State Elementary School 14 Ulakan Tapakis. Key informant in this research is class VI teacher, while the next informant is grade VI student which is taken based on the suggestion of key informant. Data collection techniques used interviews, and documentation, while to test the validity of data used triangulation technique. Based on the result of the research are students' learning difficulties are caused by internal and external factors. The interent factor is a factor from the students themselves; they are cognitive, effective, psychotic. and external factors, namely those that arise from outside the learner's self, such as the family environment, village/community environment. The efforts that can be use by teachers in overcoming the learning difficulties of class VI students at SDN 14 Ulakan Tapakis are given tasks or instructions in detail, teach the main idea of the lesson, provide physical contact/reword..